Les novellisations de Bordage : expérimentations transmédiatiques du multimédia dans la science-fiction française - Aurélie Huz (ReS Futurae)
This paper deals with the two novelizations written by Bordage, one adapted from an adventure video game (Atlantis. Les fils du rayon d’or, 1998), the other adapted from a computer-generated 3D movie (Kaena, la prophétie, 2003). Theses novels are published at a time when French novelizations are still very uncommon in popular and media culture in France (especially in science fiction), while translated imported American novelizations begin to be recognized in France as an autonomous cultural and editorial phenomenon in the middle of 1990s. In this context, due to his precedent literary success (Les Guerriers du silence, 1993-1995), Bordage offers a profitable investment to create crossmedia and transmedia projects and to associate the potential of the literary writing with the multimedia revolution of “new images” (digital 3D images, CD-ROM, video game), resulting in transmedial experimentations such as online editing, digital serial novels or script writing. Nevertheless, Bordage legitimates his own novelizations in an ambiguous way. He promotes the originality of these modern multimedia projects and, at the same time, rejects the usual criticisms directed at novelization by the French science fiction amateur scholars, on account of its links with commercial and industrial science fiction called sci-fi. Writing novelization is an intermedial way, for Bordage, to assert his narrative and xenoencyclopedial own literary signature by defending his skills as an excellent fiction storyteller and as a builder of imaginary worlds.